Seedling and adult plant resistance to leaf rust in some Bulgarian common wheat lines - V. Ivanova (Вавиловский журнал генетики и селекции)
The response of 250 common winter wheat breeding lines was investigated for resistance to the causative agent of Puccinia triticina under conditions of an infected field on the territory of Dobrudzha Agricultural Institute – General Toshevo, Bulgaria, during three successive seasons. Twenty lines with different degrees of resistance under field conditions were selected. Multi-pathotype testing was used to study the response of these lines at seedling stage under greenhouse conditions to individual pathotypes of P. triticina. Based on the response of the lines at seedling and adult stages, we found out that 20 % of them carried race-specific resistance. One of the lines (99/08-52) reacted with full resistance to the pathotypes used under greenhouse conditions. The reaction demonstrated by this line coincided with the response of isogenic lines carrying the genes Lr9, Lr19, Lr22a, Lr22b and Lr25. The other three lines (19/06-108, 82/08-43 and 82/08-35) showed a resistant reaction to 6 or 5 of the pathotypes used in the study. Their response partially coincided with the reaction of 5 isogenic lines, and the presence of some of these genes in the above lines is quite possible. Lines carrying this type of resistance are to be subjected to further genetic and breeding investigations to prove the presence of a race-specific gene. Twenty-five percent of the lines combined partial race-specific resistance at seedling stage with the resistance of race non-specific nature at adult stage. Forty percent of all studied lines carried race non-specific resistance, and 15 % of the lines possessed resistance of the “slow rusting” type. As a result of the study we carried out, the lines that demonstrated stable resistance to leaf rust can provide sufficient protection of the host and can be included in the breeding programs for developing varieties resistant to P. triticina.